PREPARATION AND STORAGE OF SALTED AND DRIED PRODUCTS OF FRESHWATER FISH, GUDUSIA CHAPRA (HAMILTON, 1822) - SHARMA, PRANJYOTI; KASHYAP, DIPANJAN; U. C. GOSWAMI (The Bioscan, 2013)
Biochemical and organoleptic quality of dry salted fish products prepared from Gudusia chapra were evaluated during storage. During the storage period Total Volatile Base Nitrogen (TVBN) value for dry salted samples varied from 21.43mg% to 98.24mg%, for wet salted samples from 25.06mg% to 114.54mg% and for unsalted samples from 32.48 mg% to 148.30 mg%. Alpha Amino Nitrogen (AAN) values at the end of storage period recorded were 137.80mg%, 160.20mg% and 189.56mg% for dry, wet and unsalted samples respectively. Free Fatty Acid (FFA) content (% of total lipid as oleic acid) at the end of storage was 28.34% for dry salted samples, 34.72% in wet salted samples and 42.10% in unsalted samples. A marginal decrease of salt content was recorded in both dry and wet samples. Sensory evaluation indicates that among the three products dry salted products were found to be superior.